Age-related differences in cranial sexual dimorphism in contemporary Europe - Velemínská, Jana; Fleischmannová, Nikola; Suchá, Barbora; Dupej, Jan; Bejdová, Šárka; Kotěrová, Anežka; Brůžek, Jaroslav (International journal of legal medicine, 2021)
Biomechanical load and hormonal levels tended to change just like the soft and skeletal tissue of the elderly with age. Although aging in both sexes shared common traits, it was assumed that there would be a reduction of sexual dimorphism in aged individuals. The main goals of this study were (1) to evaluate age-related differences in cranial sexual dimorphism during senescence, (2) to determine age-related differences in female and male skulls separately, and (3) to compare skull senescence in Czech and French adult samples as discussed by Musilová et al. (Forensic Sci Int 269:70-77, 2016). The cranial surface was analyzed using coherent point drift-dense correspondence analysis. The study sample consisted of 245 CT scans of heads from recent Czech (83 males and 59 females) and French (52 males and 51 females) individuals. Virtual scans in the age range from 18 to 92 years were analyzed using geometric morphometrics. The cranial form was significantly greater in males in all age categories. After size normalization, sexual dimorphism of the frontal, occipital, and zygomatic regions tended to diminish in the elderly. Its development during aging was caused by morphological changes in both female and male skulls but secular changes must also be taken into account. The most notable aging changes were the widening of the neurocranium and the retrusion of the face, including the forehead, especially after the age of 60 in both sexes. Sexual dimorphism was similar between the Czech and French samples but its age-related differences were partially different because of the population specificity. Cranial senescence was found to degrade the accuracy of sex classification (92-94%) in the range of 2-3%.
Keywords: určení pohlaví podle kostry; mladý dospělý; Humans; lidé; Sex Determination by Skeleton; Czech Republic; lidé středního věku; stárnutí; počítačová rentgenová tomografie; Tomography, X-Ray Computed; Middle Aged; Aging; Female; Male; Adult; Francie; France; mužské pohlaví; remodelace kosti; Aged; pohlavní dimorfismus; lebka; ženské pohlaví; Skull; Young Adult; dospělí; Sex Characteristics; Česká republika; Bone Remodeling; senioři